Hubungan Durasi Penggunaan Gadget dengan Kejadian Mata Lelah (Astenopia) pada Remaja SMAN 1 Garut - Buyung Reza Muhammad; Andri Nugraha; Eti Suliyawati; Risma Yulyyawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Continuous use of gadgets over a long period of time can emit short waves of high energy which can penetrate the eyes and ultimately cause photochemical damage to retinal cells. Excessive use of gadgets will have a negative impact on teenagers, one of which is a decline in eye health. Asthenopia is a disease experienced by the eye because the eye muscles are forced to work hard, especially when they have to look at close objects for a long time. The aim of this research is to determine the relationship between the duration of gadget use and the incidence of eye fatigue (asthenopia) in teenagers at SMAN 1 Garut. The research method used was a quantitative approach with a cross sectional research design. The population in this study was 1374 students and a sample of 94 respondents was obtained using puposive sampling techniques. Data was collected using a gadget usage duration questionnaire and a Visual Fatigue Index (VFI) questionnaire, then the data was analyzed using the Chi Square test. The results of this study show that there is a significant relationship between the duration of gadget use and the incidence of eye fatigue (asthenopia) with a p-value = 0.000 where p <0.05. So it can be concluded that there is a relationship between the duration of gadget use and the incidence of eye fatigue (asthenopia) in teenagers at SMAN 1 Garut. This research is useful as insight that there are negative impacts from excessive use of gadgets, so it is recommended that teenagers apply time limits on gadget use to prevent an increase in the incidence of asthenopia.